1987
DOI: 10.1017/s0950268800061859
|View full text |Cite
|
Sign up to set email alerts
|

Experimental infection of badgers (Meles meles) withMycobacterium bovis

Abstract: SUMMARYThe intradermal inoculation of four badgers with small numbers of Mycobacterium bovis resulted in localized lesions with ulceration which slowly healed by 5 months after inoculation. Lesions of generalized tuberculosis were seen in three badgers, one of which died at 17 months post-inoculation and in the remaining two killed 22 months post-inoculation. In the fourth badger lesions were confined to the draining lymph node of the inoculation site but M. bovis was isolated from the liver. Monthly clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 16 publications
(19 reference statements)
2
15
0
Order By: Relevance
“…The marked seasonal variation in body weight of adult badgers has been previously noted from limited studies in both free-living [8,14,15] and captive animals [13,14] with the lowest body weights being found in midsummer and the highest from November to December. The extensive body weight data from the current study have allowed a far more precise estimation of this variation both by sex and age group.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…The marked seasonal variation in body weight of adult badgers has been previously noted from limited studies in both free-living [8,14,15] and captive animals [13,14] with the lowest body weights being found in midsummer and the highest from November to December. The extensive body weight data from the current study have allowed a far more precise estimation of this variation both by sex and age group.…”
Section: Discussionmentioning
confidence: 73%
“…These badgers tended not to survive as long as those diagnosed from other samples. This may imply a more rapidly disseminated form 16 of tuberculosis, perhaps due to haematogenous spread, following inoculation of the organism, as is seen in experimentally inoculated badgers [13]. These findings support the results of a previous study based on post-mortem examinations, in which it was considered that infection originating from bite wounds accounted for 141 % of tuberculous badgers [20] and that the post-mortem appearance in these animals suggested that a particularly severe and acute form of tuberculosis resulted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even in laboratory studies, badgers may live several years without evidence of clinical disease (Corner and Presidente, 1980;Pritchard et al, 1987;Buddle et al, 1994). The opossum may be similarly affected when exposed to M. bovis, although its role as a reservoir host remains to be seen and our study was too short to assess long-term infection.…”
Section: Discussionmentioning
confidence: 96%